2012
DOI: 10.1128/iai.00181-12
|View full text |Cite
|
Sign up to set email alerts
|

The A Subunit of Escherichia coli Heat-Labile Enterotoxin Functions as a Mucosal Adjuvant and Promotes IgG2a, IgA, and Th17 Responses to Vaccine Antigens

Abstract: ABSTRACTEnterotoxigenicEscherichia coli(ETEC) produces both heat-labile (LT) and heat-stable (ST) enterotoxins and is a major cause of diarrhea in infants in developing countries and in travelers to those regions. In addition to inducing fluid secretion, LT is a powerful mucosal adjuvant capable of promoting immune responses to coadministered anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(106 citation statements)
references
References 64 publications
6
96
1
1
Order By: Relevance
“…In particular, the frequencies of IFN-␥-secreting cells and IL-17 secretion levels were higher in cells obtained from mice immunized with the DB fusion. Even if dmLT has the capacity of eliciting IL-17 responses by itself (36), the presence of the adjuvant in both formulations indicates the possibility that the fusion could be recognized by the immune system in a different manner than the individual proteins. Most importantly, this demonstrates that the DB fusion has a unique advantage in the generation of cell-mediated immunity, which can be important for control of Shigella.…”
Section: Figmentioning
confidence: 99%
“…In particular, the frequencies of IFN-␥-secreting cells and IL-17 secretion levels were higher in cells obtained from mice immunized with the DB fusion. Even if dmLT has the capacity of eliciting IL-17 responses by itself (36), the presence of the adjuvant in both formulations indicates the possibility that the fusion could be recognized by the immune system in a different manner than the individual proteins. Most importantly, this demonstrates that the DB fusion has a unique advantage in the generation of cell-mediated immunity, which can be important for control of Shigella.…”
Section: Figmentioning
confidence: 99%
“…The question still remains how dmLT with its minimal ADPribosylating activity (11,38) can be as potent as CT in inducing mucosal immune responses. In an attempt to elucidate the adjuvant mechanism of dmLT, Norton et al (11) reported that the mutations in the dmLT molecule that prevent the proteolytic cleavage of LTA subunit into A1 and A2 subunits also led to rapid degradation of the A subunit in the cytosol of intestinal epithelial cells (11).…”
Section: ⌬Ctmentioning
confidence: 99%
“…The A subunit is made up of two components, A1 and A2. The A1 subunit (21 kDa), the enzymatically active portion of the toxin, is noncovalently linked to the B pentamer via the A2 peptide (7 kDa) (10)(11)(12).…”
mentioning
confidence: 99%